Preface – Noise in the working and living environment - ZAWIESKA, Wiktor (Archives of Acoustics, 2013)
Noise is one of the most common physical risks in the workplace. Long-term exposure to its high levels can pose a significant threat to workers’ health, including hearing loss. According to the report State of the Environment in Poland 2011. Signals, trends in environmental noise indicate an increased risk of traffic noise as well as reduced growth or downwards trendsin industrial noise. Noise seems to be the environmental factor that is the greatest nuisance. This issue of Archives of Acoustics is dedicated to the problems of noise; it brings full texts of selected papers presented at the XVI International Conference Noise Control 2013.